A Singular Antiquity. Archaeology and Hellenic Identity in Twentieth-Century Greece. (Benaki Museum, 2008)
A Singular Antiquity is an attempt to investigate the ideological strategies, somewhat improvised yet at times quite effective, through which the materiality of Greek archaeology has been employed as the foundation for the metaphysics of Greekness.